Efficiency and Its Determinants: Panel Data Evidence from the Indian Pharmaceutical Industry. (February 2018) - Mahajan, Varun; Nauriyal, D. K.; Singh, S. P.
The study determines the efficiency of Indian pharmaceutical firms and its determinants in the pre- and post-product patent regime. Overall inefficiency in the industry is higher due to the inefficient conversion of inputs into output rather than through scale inefficiency. The study finds that the Product Patent Act has a negative impact on efficiency. Ownership, capital imports intensity and size variables are positively related with efficiency scores whereas age, time dummy and size square variables are inversely related. The study supports the finding that with an increase in mergers and acquisitions, a movement towards diversifying operations, the use of advanced imported foreign technology, investment in fixed assets and judicious allocation of resources for marketing activities could improve firm performance. For future policy implications, the small firms may either merge into bigger entities or manufacture pharmaceutical products for other companies, so as to raise operational scale and improve capacity utilisation. JEL Classification: C02, C61, D2, L65